QoE Evaluation: The TRIANGLE Testbed Approach - Díaz Zayas, Almudena; Panizo, Laura; Baños, Janie; Cárdenas, Carlos; Dieudonne, Michael (Wireless Communications and Mobile Computing, 2018)
This paper presents the TRIANGLE testbed approach to score the Quality of Experience (QoE) of mobile applications, based on measurements extracted from tests performed on an end-to-end network testbed. The TRIANGLE project approach is a methodology flexible enough to generalize the computation of the QoE for any mobile application. The process produces a final TRIANGLE mark, a quality score, which could eventually be used to certify applications.